Mitral valve leaflet clipping in patients with previously implanted heart failure devices - Ya. Sh. Karamova; T. M. Uskach; T. E. Imaev; S. N. Tereshchenko (Евразийский Кардиологический Журнал, 2024)
Introduction. Modern clinical guidelines for heart failure consider a comprehensive approach to treatment using implantation of various devices (cardiac resynchronisation therapy CRT, implantation of cardioverter-defibrillator (ICD), installation of pacemakers (ECS) as well as correction of valve defects. For example, for treatment of severe mitral valve insufficiency the technique of clipping its flaps using MitraClip system is used.   Objective. To evaluate the effect of mitral valve intervention with the help of MitraClip on the course of chronic heart failure (CHF) in patients with implanted devices.   Materials and Methods. 73 patients with mitral regurgitation of 3-4 degree, heart failure of II-IV NYHA functional class who underwent implantation of MitraClip system on mitral valve flaps were included in the study. The dynamics of EchoCG parameters, exercise tolerance, diuretic therapy and brain natriuretic pro-peptide level was evaluated during six months. The comparison of the results of follow-up of the group of patients who had previously been fitted with ECS, ICD, CRT (group A) with the data of patients without implanted devices (group B) was carried out.   Results. Clinical improvement of the course of CCN occurred after 6 months in both observation groups. The mean functional class (FC) of CHF decreased in group A from 2.67 ± 0.8 to 1.81 ± 0.7 (p<0.001) and in group B from 2.72 ± 1.97 (p < 0.001) to 1.86 ± 0.6, exercise tolerance increased significantly (6-minute walk test distance values increased from 299 [178; 340] m to 390 [231.3; 420] m and 235.5 [182.8; 370.3] m (p = 0.04) to 362.3 [270; 412.7] m (p = 0.03), respectively. EchoCG analysis in both groups showed no dynamics of myocardial contractility. In group A there was an increase in stroke volume (SV) from 44 [37; 63] ml to 58.5 [49.5; 84.3] ml (p = 0.03) and a decrease in pulmonary artery pressure (PAP) from 44 [35; 62.5] mm Hg to 39 [29.8; 45] mm Hg (p = 0.02). In group B, in addition to an increase in SV from 57.5 [48.8; 65.3] ml to 61 [52; 74.5] ml (p = 0.03) and a decrease in PAP from 45 [36.5; 59.3] mm Hg to 32 [27.3; 43.5] mm Hg (p < 0.001), an increase in cardiac output (CO) from 4 [3.3; 4.8] L/min to 4.5 [3.6; 5.3] L/min (p = 0.04) and a significant decrease in left atrial and left ventricular dimensions and volumes were obtained.   Conclusion. Application of the system of MC leaflet clipping for correction of severe MR leads to improvement of clinical condition in patients with CHF both with and without implanted devices. Absence of significant dynamics of heart chamber sizes and volumes according to EchoCG data in patients with implanted devices is most likely due to small sample size.